2007
DOI: 10.1002/adfm.200700019
|View full text |Cite
|
Sign up to set email alerts
|

Resorbable Dicalcium Phosphate Bone Substitutes Prepared by 3D Powder Printing

Abstract: Bioceramic bone substitutes with programmed architecture were manufactured at room temperature in this study using a novel 3D printing process that combined 3D powder printing with calcium phosphate cement chemistry. During printing, biphasic α/β‐tricalcium phosphate (Ca3(PO4)2, TCP) powder reacted with a liquid component consisting of phosphoric acid solution to form a matrix of dicalcium phosphate dihydrate (CaHPO4·H2O, DCPD, brushite) and unreacted TCP. Printed samples showed compressive strengths between 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
204
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(220 citation statements)
references
References 35 publications
(27 reference statements)
6
204
2
4
Order By: Relevance
“…Previously published research on scaffolds printed in this way, using the same raw materials, suggests the presence of monetite within the structures. It was reported that hydrothermal conversion of brushite to monetite led to an increase in porosity of approximately 13 % [42]. Although monetite formation was not detected in the work presented here, the increase in porosity is suggestive of CaP dissolution, a process which may or may not reach equilibrium before the media are refreshed every 3 days.…”
Section: Effect Of Immersion In Unsupplemented Media On Cap Discscontrasting
confidence: 38%
“…Previously published research on scaffolds printed in this way, using the same raw materials, suggests the presence of monetite within the structures. It was reported that hydrothermal conversion of brushite to monetite led to an increase in porosity of approximately 13 % [42]. Although monetite formation was not detected in the work presented here, the increase in porosity is suggestive of CaP dissolution, a process which may or may not reach equilibrium before the media are refreshed every 3 days.…”
Section: Effect Of Immersion In Unsupplemented Media On Cap Discscontrasting
confidence: 38%
“…Tissue engineering with 3D printed bioceramics loaded with BM and O 2 loaded PFD 3D-printed CPCs offer a unique opportunity to treat complicated bone defects by designing the implant according to the specific required geometry (Gbureck et al, 2007a). In previous studies we have shown the osteconductive and osteoinductive potential of 3D printed CPCs on goat vertebrae (Habibovic et al, 2008), and we have also been able to augment craniofacial bones using this 3D printed materials (Tamimi et al, 2009a).…”
Section: Oxygen Delivery In Vitromentioning
confidence: 99%
“…Tubular brushite ceramic blocks were 3D-printed as per the computer design (Fig. 1B-C), following a previously reported technique for cement printing (Gbureck et al, 2007a).…”
Section: In Vivo Implantation Of Pfd Loaded Bioceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Last century, sintered ceramics such as calcium phosphates were the most commonly used hard tissue biomaterials from the viewpoint of mechanical strength; however, they are fundamentally less biodegradable and not easy to process. To obtain better handling properties, apatite-collagen/ gelatin composites [7][8][9] in addition to various kinds of calcium phosphate cements [10][11][12] have been developed. Recently, tissue engineering has been developed.…”
Section: Introductionmentioning
confidence: 99%